Integrating schools as community hubs: planning strategies and implementation challenges in South Korean new towns - Nami Hong; Sanghoon Jung (Journal of Asian Architecture and Building Engineering)
This study examines how schools can be effectively integrated as community hubs within the urban planning frameworks of South Korean new towns, particularly focusing on Byeolnae, Gwanggyo, and Sejong. Through a comparative case study approach, using field surveys, stakeholder interviews, and archival analysis, the study identifies the evolution of planning strategies and implementation challenges of school-oriented development. The study reveals three key dimensions of development: openness and connectivity, multifunctionality and integration, and stakeholder collaboration. While Byeolnae pioneered the community corridor concept, Gwanggyo enhanced facility integration within school sites, and Sejong achieved the most comprehensive integration through clustered community complexes. The findings highlight that successful implementation requires not only strategic location selection and detailed urban design guidelines but also robust integrated governance frameworks to align diverse stakeholder interests. The study contributes to theoretical understanding of school-community integration and practical insights for future development, emphasizing the importance of coordinated planning, construction, and operational frameworks in creating sustainable school-oriented community hubs.